Offenses against the rights of employees – comments on the regulations of the Penal Code and the Code of Criminal Procedure - Izydorczyk, Jacek (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The article presents the current state of protection provided in the Penal Code (Chapter XXVIII) of employees – along with the new controversial provision of Art. 218a Penal Code. The article also points to the issue of proceeding in a criminal trial regarding such crimes.